Estrategias de comunicación para la promoción del carnaval intercultural de la unión de organizaciones de desarrollo integral unión y progreso, cantón Guaranda provincia Bolívar año 2019 - Aguilar Saltos, Gloria Angélica (2020)
The intercultural carnival or also known as Pawkar Raymi, a holiday that is held in gratitude to the Pacha Mama (mother earth) for her generosity with the communities by allowing them to obtain good harvests, this is practiced by the Andean peoples in Ecuador are celebrated in barrios parts like in: Chimborazo, Imbabura, Carchi, Cotopaxi among other provinces such as in Bolívar, especially in Guaranda, communities such as Rayo, Quinua Coral, El Sinche, San Francisco, among others, where they celebrate with traditional rituals and dances thanking all the breasts and taitas (taita inti (sun), mama yaku (water), taita waira (wind) among others) of the Andean worldview that have allowed the flowering of their crops and have given them the happiness of having good products. This holiday includes the experiences and traditions of the Andean people, allowing them to connect with their ethnic roots and somehow encourage the preservation of the culture of the towns such as: gastronomy, singing, music, dances, folklore that characterize them, preventing identity from being lost. of people. The intercultural carnival is known as the March Equinox or Pawkar Raymi, the Pachamama is celebrated, in this sense, it should be noted that the rains generally begin, in the Andes area, in November, so that in March those Rains produce fruits and flowers. Thus, the March equinox represents a time of harvest in the southern hemisphere and throughout Ecuador